The Reduction of Stress Concentration at a Crack Tip Using Multi Stop-Drilled Hole (MSDH) - Dahlan, Hendery; Rusli, Meifal; Bur, Mulyadi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
A new shape of stop-drilled hole is proposed in which triple stop-drilled holes called Multi Stop Drilled Hole (MSDH) are drilling at the crack tip. The main objective of the proposing method is to reduce stress concentration at the edge of the stop holes. Reducing the stress concentration factor at the crack tip is the main issue to arrest the crack growth. In this study, a numerical methodology using finite element analysis with linear elastic behaviour assumption is considered to study the effect of the stop-drilled hole on the reduction of stress concentration at crack tip. The variation number of stop-drilled hole and hole diameter at the crack tip corresponding to the stress concentration will be investigated. It reveals that the number of stop-drilled holes significantly influenced to reduce the stress concentration factor. Increasing the number of the stop-drilled holes will reduce the stress concentration factor. Furthermore, the diameter of stop hole significantly affects the decreasing stress concentration. The increasing value diameter of the stop-drilled hole will reduce the stress concentration. In the meantime, the triple-drilled hole has the highest percentages of decreasing stress concentration and the lowest stress concentration comparing to single and double stop-drilled hole.